2019
DOI: 10.17221/508/2019-pse
|View full text |Cite
|
Sign up to set email alerts
|

Co-application of molybdenum and zinc increases grain yield and photosynthetic efficiency of wheat leaves

Abstract: The effects of the co-application of molybdenum (Mo) and zinc (Zn) on winter wheat grain yield, leaf photosynthetic efficiency, and antioxidant activity were investigated using pot culture experiments with sandy soil. Four treatments were investigated, including a control (CK), 0.15 mg Mo/kg soil (Mo), 1 mg Zn/kg soil (Zn), and 0.15 mg Mo/kg + 1 mg Zn/kg soil (Mo + Zn). The results showed that the soil application of Mo and Mo + Zn increased the winter wheat grain yield, spike number, and thousand kernel weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…Our results are also supported by those of Liu et al [61]. They documented an increased photosynthetic efficiency by increasing chlorophyll a and b concentrations due to Zn application in Zn-deficient soil [61].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are also supported by those of Liu et al [61]. They documented an increased photosynthetic efficiency by increasing chlorophyll a and b concentrations due to Zn application in Zn-deficient soil [61].…”
Section: Discussionsupporting
confidence: 92%
“…Our results were also supported by Liu et al [48] he reported increased in photosynthetic e ciency by increasing chlorophyll a and b contents due to Zn application in Zn de cient soil [48]. Zinzala et al [47] reported that above 80 mg Zn kg -1 soil application, all physiological parameters negatively affected due to the toxicity of Zn in plant tissues [47].…”
Section: Discussionsupporting
confidence: 86%
“…Foliar treatment of French bean plants with organic and inorganic salts of iron increased the content of the sum of chlorophylls а and b and carotenoids in leaves (Borowski E and Mihalek, S 2011). A considerable increase in the content of both chlorophyll forms and carotenoids was determined in winter wheat leaves in the sand culture after the introduction of either molybdenum or zinc into soil or their combined application (Liu C et al, 2019). Higher accumulation of chlorophyll and carotenoids in wheat leaves was determined under low temperature stress and treatment with Mo, compared against the control variant (Sun X, 2006; Yu M et al, 2006).…”
Section: The Impact Of Trace Elements On the Indices Of соmentioning
confidence: 99%
“…The fi rst genotype also had the increased SOD activity (Hamurcu M et al, 2017). It was demonstrated using sandy substrate that after the introduction of zinc into soil or its combined application with molybdenum there was a considerable increase in the activity of SOD, CAT and peroxidase (KF 1.11.7) in wheat leaves (Liu C et al, 2019). Under osmotic stress, simulated by polyethyleneglycol in the hydroponics culture, the variants with the application of Mo demonstrated a considerable increase in the activity of several antioxidant enzymes (SOD, peroxidase, CAT, ascorbate peroxidase (APO, KF 1.11.1.11)) in the winter wheat cultivar with a not high content of molybdenum, but when the Mo content was high, the difference from the control was signifi cant only on some dates.…”
Section: The Impact Of Trace Elements On Antioxidant Enzymesmentioning
confidence: 99%
See 1 more Smart Citation